Dialectic Development Models of Humanity's Destiny - Normatova Nodira Suyundikovna (Scientific Trends, 2025)
The article discusses the concepts of the biosphere and the noosphere, their stages of evolutionary development. The causes and consequences of environmental problems are analyzed based on scientific and philosophical views. The evolutionary development of human civilization is based on the stages.
Keywords: Biosphere, noosphere, evolution, ecophilosophy, dialectics, development model, moral philosophical aspect, technological futurological aspect, socio-political aspect, evolution, ecological problems.